A Dynamic Typology of Informal Institutions: Learning from the Case of Guanxi. (14th July 2016) - Horak, Sven; Restel, Katja
ABSTRACT: Currently, the mechanism in which informal institutions, recently discovered as an influential, new paradigm in business and management studies interact with and shape formal institutions remains unclear. Helmke and Levitsky (2004 ) proposed an outcome-based typology for the interaction of informal institutions with formal ones. By using a structured approach for literature aggregation, we test the proposed typology of Helmke and Levitsky by applying this method to 74 empirical studies to investigate the influence of guanxi on formal institutions. We conclude that guanxi fits into none of the proposed categories perfectly. As a result, we propose the relationship between guanxi and formal institutions as auxiliary as well as competing concurrently, leading to convergent and divergent outcomes, respectively. Moreover, we propose a third category to add to the existing typology, namely 'formal institutions in transition'. We furthermore incorporate a dynamic aspect to the model by adding two further categories, concerned with the direction of the development. We believe the resulting extension to the original typology of Helmke and Levitsky accurately accounts for the dynamic nature of informal institutions as well as their important role in shaping effective formal institutions.